2009
DOI: 10.1149/1.3216049
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Stability of Low Temperature Transparent Thin-Film Transistors Using Amorphous Multicomponent Dielectrics

Abstract: High performance transparent thin-film transistors deposited on glass substrates and entirely processed at a low temperature not exceeding 150°C are presented and analyzed in this paper. Besides being based on an amorphous oxide semiconductor, the main innovation of this work relies on the use of sputtered multicomponent oxides as dielectric materials based on mixtures of Ta 2 O 5 with SiO 2 or Al 2 O 3 . These multicomponent dielectrics allow to obtain amorphous structures and low leakage currents while prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 56 publications
2
57
0
Order By: Relevance
“…15,16 Some groups pointed out that the charge trapping at the semiconductor/gateinsulator interface plays an important role in the V th instability of oxide TFTs. 15,16,[21][22][23] Our results revealed that the deep traps are easily generated at the ZnO/gate insulator interface. The interface treatment reported in this article would affect the reliability of the ZnO TFTs.…”
Section: H103mentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Some groups pointed out that the charge trapping at the semiconductor/gateinsulator interface plays an important role in the V th instability of oxide TFTs. 15,16,[21][22][23] Our results revealed that the deep traps are easily generated at the ZnO/gate insulator interface. The interface treatment reported in this article would affect the reliability of the ZnO TFTs.…”
Section: H103mentioning
confidence: 99%
“…[14][15][16] Particularly, subthreshold characteristics such as the V th and subthreshold swing essentially depends on the semiconductor/gate-insulator interface traps. The channel/gateinsulator interface in a-Si:H TFTs is formed within a vacuum by plasma-enhanced chemical vapor deposition ͑PECVD͒; however, that in oxide TFT is usually formed with a vacuum break because the oxide semiconductor is usually deposited by sputtering on the gate insulator which was formerly deposited by PECVD.…”
mentioning
confidence: 99%
“…High-k materials are desirable because their added capacitance can compensate for the higher density of interface traps and, thus, improve the transistor performance, namely, decrease the subthreshold swing (SS) and the operating voltage [17]. However, most of the high-k dielectrics (such as HfO 2 , ZrO 2 , and Ti 2 O 5 ) present a polycrystalline structure, which can result in an inferior dielectric reliability, because grain boundaries act as preferential paths for impurity diffusion and leakage current [18]. Besides, high-k dielectrics often suffer from low breakdown voltage and high leakage current, due to lower bandgap (E g ) and smaller band offsets (relatively to the semiconductor) than traditional SiO 2 and SiN x :H [19].…”
Section: Introductionmentioning
confidence: 99%
“…Among various amorphous semiconductor oxides, gallium-indium-zinc-oxide (GIZO) as the TFT active layer is gaining significant importance. The interesting properties associated with the a-GIZO TFT technology are fabrication at room-temperature [4], [5], better optical transparency and the relatively high mobility. These a-GIZO TFT applications are not only confined to displays (AMOLED) [6], but also extended to sensors [7].…”
Section: Introductionmentioning
confidence: 99%